The Utilization of Audiovisual Media in Improving Short Story Writing Skill of Fourth Grade Students at Elementary School - Papuanga, Kiswita; Notanubun, Zainudin; Ririhena, Ribka L (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The abstract nature of storytelling and a lack of engaging learning media often lead to low writing skills among elementary school students. At Elementary School 2 Poka, students faced significant challenges in organizing storylines and developing ideas, as evidenced by low initial test scores. This study aims to enhance short story writing skills through the utilization of audiovisual media in Indonesian language learning. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each comprising planning, acting, observing, and reflecting. There were 25 fourth-grade students in the study. Data was collected through classroom observations, short story writing tests, and documentation, then analyzed using mixed descriptive quantitative and qualitative methods. The indicator of success was set at 85% of students reaching the minimum mastery criterion of > 70. The findings revealed a progressive improvement in students' performance. The average score went up from 47.6 in the pre-test to 67.6 in Cycle I and then to 81.2 in Cycle II. Correspondingly, classical completeness increased significantly from 24% at the baseline to 52% in Cycle I, finally achieving 88% in Cycle II. The integration of audiovisual media effectively assisted students in visualizing story elements, structuring coherent plots, and refining their diction. This study demonstrates that audiovisual media is an effective pedagogical tool to boost interest, motivation, and creative writing skills. These results provide a practical reference for elementary educators to adopt multimedia-based strategies to overcome barriers in literacy education.